Consumption patterns and usage of selected underutilized legumes in a Ghanaian community - Pearl Boamah Agyekum; Jannika Dombrowski; Herman E. Lutterodt; Isaac W. Ofosu (Legume Science, 2023)
Abstract Underutilized legumes are a good source of plant proteins, but they exhibit a hard‐to‐cook nature and poor digestibility due to the presence of anti‐nutritional factors. This study focused on the factors that drive the utilization of selected underutilized legumes in the Techiman municipality of Ghana. The legumes studied were Vigna subterrenea (Bambara groundnut), Cajanus cajan (Pigeon pea), Phaseolus lunatus (Lima bean), Parkia biglobosa (African Locust bean), and Canavalia gladiata (Sword bean). The survey provided insight into the familiarity, uses, preparation methods, and the extent of knowledge of their nutritional benefits. The demographics of the participants studied were also described, and statistical analysis was done using descriptive statistics. The results showed that the legumes were well recognized despite their underutilized status and they find use primarily in domestic savory food preparation. Consumption was mostly occasional despite the knowledge of its nutritional benefits. Processing mainly referred to boiling with prior removal of foreign materials and soaking in water. Nutrition stood out as the most desired property. Strategies aiming at maximizing the use of these legumes must be considered and developed since these legumes appear to be a formidable resource for combating the prevalent food insecurity in Africa.